Europarl: Swedish-Italian - Språkbanken Text (University of Gothenburg, 2024)
Part of European Parliament Proceedings Parallel Corpus

Del av European Parliament Proceedings Parallel Corpus
Europarl: svenska-italienska
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik